Nilai-Nilai Pendidikan Dalam Komik “Demon Slayer” Dan Relevansinya Dengan Pendidikan Agama Islam - Fitroh Rahmat Setiawan; Risma Nisa Insyiroh; Riza Faishol (PT. Nawa Edukasi Nusantara, 2026)
This study aims to examine the relevance of educational values depicted in the comic Demon Slayer: Kimetsu no Yaiba to the concept of Islamic Religious Education (PAI). The main problem discussed focuses on how the moral, spiritual, and humanitarian values found in Demon Slayer can be integrated into Islamic education, which is rooted in the Qur’an and Hadith. This research employs a qualitative descriptive method using content analysis. Data sources were drawn from the comic’s narrative and visual elements, supported by scholarly literature. The findings reveal that values such as patience (ṣabr), empathy (raḥmah), sincerity (ikhlāṣ), responsibility (mas’uliyyah), hard work (ijtihād), and family love align closely with Islamic moral principles. Although Demon Slayer emphasizes humanistic and empirical learning, its values can serve as contextual educational tools within Islamic Religious Education when directed by divine principles. The study concludes that popular media like comics can function as effective pedagogical alternatives to instill spiritual awareness and Islamic character education among modern learners.